Use of ascorbic acid (vitamin C) and alpha tocopherol (vitamin E) as adjuvants in the treatment of neuropathic pain - Fernando Antonio Silva de Azevedo-Filho; Yasmim Machado Chaves de Castro; Marcos Pinho Cerqueira; Thiago Arruda Rodrigues; Yussef Ali-Abdouni; Patrícia Maria de Moraes Barros Fucs (BrJP)
BACKGROUND AND OBJECTIVES: High concentrations of free radicals can damage nucleic acids, proteins and lipids and their accumulation may be involved in hypersensitivity to pain. The objective of this study was to evaluate the effect of vitamins C and E as adjuvants in the treatment of neuropathic pain. METHODS: This study included 98 patients with neuropathic pain, classified by the Douleur Neuropathique 4 Questions (DN4), randomized into two groups: control and intervention. The control group received 150 mg of pregabalin and the intervention group 150 mg of pregabalin combined with 500 mg of vitamin C and 400 mg of vitamin E. Treatment and follow-up of the participants lasted 12 weeks. At the initial assessment, the patients answered the Quick Disabilities of the Arm, Shoulder and Hand (Quick-DASH) to assess upper limb functionality; quality of life was described using the World Health Organization Quality of Life-Bref (WHOQOL-bref) and pain assessment was measured using the visual analogue scale (VAS). After 12 weeks of treatment, the patients responded to the same instruments. RESULTS: 86 patients completed treatment. Losses of participation in the sample were due to abandonment of treatment (n=7) or adverse effects to pregabalin (n=5). The intervention group presented superior results compared to the control group. Multiple comparisons between groups and moments for the evaluated scores demonstrated a mean difference from pre-treatment to post-treatment only in the intervention group (p < 0.05), with a mean reduction in Quick-DASH and VAS and a mean increase from WHOQOL. CONCLUSION: It was observed that the use of vitamin C and E in combination with pregabalin had a greater analgesic effect than the use of pregabalin alone.